DIFFERENCES IN ATTITUDES TOWARDS/BELIEFS ON COMPLEMENTARY AND ALTERNATIVE MEDICINE WITNESSED BETWEEN PHYSIOTHERAPISTS, NURSES/PARAMEDICS AND PHYSICIANS - Å½ivÄiÄ‡, Debi; Racz, Aleksandar; Dario, NaletiliÄ‡ (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The change in social order that took place in Croatia in the 1990s made medical pluralism - in terms of coexistence of various treatment options apparent. In spite of the European Commission and WHO recommendations, complementary and alternative medicine (CAM) failed to be regulated by the law, even upon EU accession. Materials and Methods: This study aimed at investigating the attitudes of healthcare professionals towards CAM, as well as possible differences in attitudes expressed by physicians, nurses/paramedics and physiotherapists and comprised a total of 325 healthcare professionals affiliated with either private or public healthcare facilities and belonging to one of the three major categories of healthcare providers under study. The study was carried out throughout 2011 - 2012, and made use of IMAQ (Integrative Medicine Attitude Questionnaire). Results: A total score seen in the physicians’ arm was statistically lower (M 91.76) when compared to that obtained in the nurses/paramedics’ (M 97.28) and the physiotherapists’ arm (M 97.27). Significant differences in CAM-related attitudes were proven to exist between physicians and nurses/physiotherapists (F=7.853921, p=0.000), but not between nurses and physiotherapists (δ=1.531, p=1.000). These differences boil down to higher criticism expressed by physicians as regards CAM efficiency, especially the therapeutic value of spiritual & intuitive curing methods and osteopathic & laying-on-hands treatments, while significant differences in attitudes towards acupuncture, chiropractic and massage failed to be found. Differences in healthcare professionals’ attitudes arising on the grounds of gender (T=-1.411, p=0.159), educational background (F=2.372303, p=0.095) and the number of years in service (F=0.833, p=0.436), failed to be seen as well. Conclusion: Despite the fairly high IMAQ score obtained in the study sample that speaks in favour of a positive rather than neutral CAM-related attitude of healthcare providers under study, the very structure of the IMAQ tool prevents us from the unbiased conclusion that Croatian healthcare providers support CAM. Physicians are far less prone to support alternative and spiritual treatment practices than nurses/paramedics and physiotherapists.